Study of the influence of surface treatment on the wear development under quasi-static loading of the levers of a newly designed thrust bearing. (June 2021) - Monkova, Katarina; Urban, Marek; Monka, Peter Pavol; Kozak, Drazan
Highlights: The self-equalizing bearing allows minimizing the misalignment of rotating components. The most critical part of the bearing being developed is the lever that was tested in this study. The observed cracks and surface damage were caused only by the surface treatment technology. Testing of samples and real levers confirmed the applicability of bearings in real conditions. Abstract: Hydrodynamic thrust bearings are generally used to absorb axial forces in machinery, especially where the use of rolling bearings is inappropriate in terms of dimensional constraints, service life, high loads or difficult access during assembly. Misalignment between the stator and the rotor, especially on large rotary machines, can lead to a reduction in the load capacity and damage to the entire device. To eliminate misalignment between stator and rotor (especially in large rotary machines) the thrust bearing with a system of very precise manufactured levers has started to be used. The article deals with the study of the influence of surface treatment on the development of wear and damage under quasi-static loading of the levers, which are critical parts of a newly designed axial bearing. The presented research has been carried out in two phases. In the first phase, basic samples that represented the types of geometries coming into contact in real conditions of bearing operation were manufactured and experimentally tested. Based on the results obtained at this stage, it was found that electroless nickel-plated samples showed the best results in terms of surface treatment. Due to this, real levers were produced in three sizes, which are estimated to have the potential for the greatest use in turbines, and these were surface treated with electroless nickel plating. In the second phase, the surface integrity and stiffness of the levers were examined. All samples and levers were made of 34CrNiMo6 steel. The evaluation was performed using stereomicroscope and a scanning electron microscope. Based on the results, it could be stated that the integrity of the surface was not significantly violated in any simple sample or lever. Thus, the tests confirmed the suitability of the proposed method of surface treatment of levers and their sufficient rigidity under quasi-static static loading.